Combined IMIG and Immune Ig Attenuate Allergic Responses in Beagle Dogs. (21st April 2020) - Gorczynski, R. M.; Maqbool, T.; Hoffmann, G.
Abstract : Background . We previously reported attenuation of serum OVA-specific IgE levels and of lymphocyte-derived IL-4, both nominal markers of allergic immunity, following injection of a combination of homologous (mouse) polyclonal anti-idiotypic immunoglobulin (Ig) and immune Ig in BALB/c mice. We predicted this might generalize to other species and using heterologous mixtures of Igs. This was assessed in mice using OVA sensitization in the presence of human Igs as a source of both anti-idiotype Ig and immune Ig and in dogs with peanut butter-induced allergic responses. Methods . Eight-week-old BALB/c mice received OVA immunization and 5 weekly injections of immune Ig or anti-idiotype Ig from either homologous (mouse) or heterologous (human) sources. Five-month-old Beagles received weekly topical exposure (on the abdomen) to peanut butter and treatment with pooled dog Ig and dog antirabies immune Ig, or a combination of human IMIG and human anti-Tet. All mice/dogs thereafter received a final allergen challenge, and serum IgG, IgE, and allergen-induced IL-2/IL-4 and IL-31 production in 72 hr cultures was measured. Results . In mice attenuation of OVA-induced allergy (IgE-specific Ig and OVA-induced IL-4) was seen using both mouse and human Ig mixtures, without effect on OVA serum IgG or OVA-induced IL-2. Attenuation of concanavalin A- (ConA-) induced IL-4 : IL-2 production and of peanut butter-induced IL-4 and IL-31 was seen in dogs receiving combinations of both heterologous and homologous immune Igs and anti-idiotype Igs, with no decline in IL-2 production. Allergen-specific IgE/IgG was not detectable in dog serum, but there was a trend to lower total serum IgE levels (and decreased IgE : IgG ratios). Conclusion . Homologous and heterologous combinations of polyclonal IMIG and immune Ig attenuate allergic responses in mice and dogs. This treatment protocol represents a novel approach which can be adapted for allergic desensitization in veterinary and human use.